FORMULASI KRIM EKSTRAK DAUN GAMBIR (Uncaria gambir Roxb.) SEBAGAI PENYEMBUH LUKA BAKAR - Thaib, Cut Masyithah; Sinaga, Taruli Rohana; Manurung, Kesaktian (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The potential for the use of gambier is expanding as the various benefits of gambier are known, such as a natural medicine for burns, tanning materials, and others. Gambir contains chemical components of tannins, saponins, and alkaloids that can help in the healing process of burns. This study aims to obtain a cream preparation of gambier leaf extract that can be used to heal burns